The Digital Dynamic Models of Linear Asynchronous Drive - Poska, A.; Rinkeviciene, R.; Teiserskas, C. (Elektronika ir Elektrotechnika, 1997)
There is presented the calculation of transient processes in linear asynchronous drive with consideration of electromagnetic transient processes in the linear synchronous motor in the case when the resistance force and moving mass depends on the way passed by the motor’s secondary element.